2020
DOI: 10.3390/ijgi9040257
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Normalized Difference Vegetation Index (NDVI) with Top-of-Canopy (TOC) Reflectance from a KOMPSAT-3A Image Using Orfeo ToolBox (OTB) Extension

Abstract: Surface reflectance data obtained by the absolute atmospheric correction of satellite images are useful for land use applications. For Landsat and Sentinel-2 images, many radiometric processing methods exist, and the images are supported by most types of commercial and open-source software. However, multispectral KOMPSAT-3A images with a resolution of 2.2 m are currently lacking tools or open-source resources for obtaining top-of-canopy (TOC) reflectance data. In this study, an atmospheric correction module fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Healthy vegetation reflects more infrared and absorbs more red and blue portions of the electromagnetic spectrum. The red and near-infrared bands are important for calculating NDVI and other vegetation indices as the blue portion is affected by atmospheric scattering [43]. In areas with a single modal annual rainfall pattern, there is less absorption of the visible light and low reflection of the infrared light during the dry season (Figure 5), resulting in low NDVI values.…”
Section: Distinguishing Irrigated From Rainfed Areasmentioning
confidence: 99%
“…Healthy vegetation reflects more infrared and absorbs more red and blue portions of the electromagnetic spectrum. The red and near-infrared bands are important for calculating NDVI and other vegetation indices as the blue portion is affected by atmospheric scattering [43]. In areas with a single modal annual rainfall pattern, there is less absorption of the visible light and low reflection of the infrared light during the dry season (Figure 5), resulting in low NDVI values.…”
Section: Distinguishing Irrigated From Rainfed Areasmentioning
confidence: 99%
“…The use of an open source software is one of the main advantage of the presented method. OTB open source software proved to be a powerful tool for OBIA using photogrammetry derived images, even if developed for other applications [39,64,65].…”
Section: Discussionmentioning
confidence: 99%
“…Among the open sources that provide atmospheric correction schemes or algorithms, the OTB provides an absolute atmosphere correction method that uses atmospheric variables. The absolute atmospheric correction method showed that the error with the field measurement of RadCalNet portal value was small, according to a comparative experiment using relative atmospheric correction and absolute atmospheric correction [46,47]. The KOMPSAT-3/3A for OTB extension was implemented [48], and the TOA and TOC reflectance products using this extension were validated with RVUS, BTCN, BSCN, and LCFR data in RadCalNet [49,50].…”
Section: Absolute Atmospheric Correction Module To Generate Reflectance Products As Saasmentioning
confidence: 99%